Iodine-Catalyzed Simple and Efficient Synthesis of 1,3,5-Triarylbenzenes and 2,3-Dihydrobenzofuran Derivatives under Mild Reaction Conditions - Cheng, Dong; Meng, Xiangzhen; Li, Dongmei; Jie, Sunying; Liu, Yifan; Jiao, Xiaoqing (Synlett, 2023)
The I2-catalyzed cyclization reaction of chalcones and 2-aryl propionaldehydes or isobutyraldehyde has been developed for the synthesis of 1,3,5-triarylbenzenes and 2,3-dihydrobenzofuran derivatives. This reaction tolerates a wide range of functional groups. Moreover, this method features an inexpensive catalyst and available starting materials.
Keywords: 1,3,5-triarylbenzenes; 2,3-dihydrobenzofuran scaffolds; chalcone; annulation; I2